Developing magnetic damper system for microsatellite - Legowo, Ari; Sulaeman, Erwin; Rosli, Muhammad Danial (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In this paper, the study of nutation damper using magnetic hysteresis is presented. There are various types of nutation damper existed and are discussed in many papers including an active nutation damper and passive nutation damper. This paper focuses only the usage of passive nutation damper because of the size limitation of microsatellite body that constraint the benefit of using active nutation control. Attitude motion of the microsatellite is described by using kinematic Euler equation where the approach of differential equation was used. The interaction of magnetic hysteresis with earth magnetic field is studied in this paper. Derivation of the governing equation in determining the attitude is briefly discussed. The effects of changing the parameter of damper characteristics as well as the effect of changing the model of the microsatellites; cylindrical and cube shape is considered. The attitude dynamics are observed by simulating the equations using MATLAB software and the results from simulation are discussed and concluded.